Analysis of physical fitness tests for police officers in various countries: a scoping review - Zhang, Zhaohua; He, Jian; Zhang, Xiaohui; Zhao, Liru; Deng, Yujian (Frontiers in Physiology, 2025)
Physical fitness tests are an essential part of police selection and retention. The aim of this study was to analyze the physical fitness tests of police officers in various countries. We systematically searched Chinese and English databases, including Web of Science, SPORTDiscus, PubMed, and CNKI, from their establishment dates to 1 December 2024. A total of 16 physical fitness tests for police officers from 7 countries were analyzed. All physical fitness tests were divided into two categories: one focused on basic fitness test items (n = 9), and the other was an obstacle courses, the main content of which simulates specific occupational tasks that police officers may need to perform on duty (n = 7). The most used components were cardiorespiratory endurance, muscular strength and endurance and agility. This review includes two distinct testing paradigms: 'General Physical Fitness’ and 'Job-Specific Competence’. It indicates that there is no universally 'optimal’ testing model. The selection or development of police physical fitness tests must be grounded in selection efficiency, ecological validity, and cultural applicability.